2017
DOI: 10.1096/fj.201601021r
|View full text |Cite
|
Sign up to set email alerts
|

Selective expression of TSPAN2 in vascular smooth muscle is independently regulated by TGF‐β1/SMAD and myocardin/serum response factor

Abstract: Tetraspanins (TSPANs) comprise a large family of 4-transmembrane domain proteins. The importance of TSPANs in vascular smooth muscle cells (VSMCs) is unexplored. Given that TGF-β1 and myocardin (MYOCD) are potent activators for VSMC differentiation, we screened for TGF-β1 and MYOCD/serum response factor (SRF)-regulated in VSMC by using RNA-seq analyses and RNA-arrays. was found to be the only family gene induced by TGF-β1 and MYOCD, and reduced by SRF deficiency in VSMCs. We also found that is highly expressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 58 publications
1
31
0
1
Order By: Relevance
“…PDGF induces the synthetic phenotype of VSMCs ( Fig 1A ) [ 1 ]. Data from HCASMs overexpressing myocardin (MYOCD) (GSE77120) and those cells treated with TGFβ (GSE85910) were obtained [ 22 ]. Both MYOCD and TGFβ were reported to induce a contractile phenotype ( Fig 1A ) [ 1 , 2 ].…”
Section: Resultsmentioning
confidence: 99%
“…PDGF induces the synthetic phenotype of VSMCs ( Fig 1A ) [ 1 ]. Data from HCASMs overexpressing myocardin (MYOCD) (GSE77120) and those cells treated with TGFβ (GSE85910) were obtained [ 22 ]. Both MYOCD and TGFβ were reported to induce a contractile phenotype ( Fig 1A ) [ 1 , 2 ].…”
Section: Resultsmentioning
confidence: 99%
“…More than one half of TSPANs family genes are significantly reduced by TGF-β1, while only TSPAN2, 12, 13, and 22 are up-regulated, and TSPAN2 shows the most dramatic change by TGF-β1 (Zhao et al, 2017). Myocardin, which is another master regulator of VSMCs differentiation, increases 8 TSPANs genes expression, including TSPAN2,7,10,11,12,15,21,33, and TSPAN2 showed the greatest up-regulation (Zhao et al, 2017). The expression profiles of TSPANs family genes in ECs and VSMCs indicate that they may play critical roles in vascular biology, such as migration ( Table 2).…”
Section: The Current Understanding Of Tetraspanins Family In Vascularmentioning
confidence: 97%
“…They found that HUVECs expressed 23 TSPANs and human liver endothelium expressed 17 TSPANs. The RNA-seq analyses and RNA-arrays for TSPANs family genes expressed in HCASMCs, MASMCs and mouse carotid arteries indicate that all TSPANs except for TSPAN16 and TSPAN19 are detectable in these cells and tissue (Zhao et al, 2017). More than one half of TSPANs family genes are significantly reduced by TGF-β1, while only TSPAN2, 12, 13, and 22 are up-regulated, and TSPAN2 shows the most dramatic change by TGF-β1 (Zhao et al, 2017).…”
Section: The Current Understanding Of Tetraspanins Family In Vascularmentioning
confidence: 97%
See 2 more Smart Citations